Executive function in early childhood: Harnessing the potential of nature-based practices to elevate and equalize outcomes - Ernst, Julie; Sobel, David; Neil, Ahna (Frontiers in Education, 2022)
This study examined the effect of nature-based practices on preschoolers’ executive function (EF). The Minnesota Executive Function Scale was administered to 147 children within one school district at the beginning and end of the preschool year. Results suggest incorporating nature-based practices into preschool was effective, as children in preschool classrooms where nature-based practices were used had significantly higher levels of EF at the end of the school year than children in programs where nature-based practices were more minimally used. Preschools that used a blended approach (some incorporation of nature-based practices) were significantly more effective than preschools that had lesser incorporation of nature-based practices. Results also point to the effectiveness of a blended approach for supporting EF in lower SES children. This study contributes to the literature regarding effective practices for supporting EF development and adds to the growing body of research surrounding the impact of nature play on child development and school readiness.